2013
DOI: 10.1007/s10147-012-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of epidermal growth factor receptor mutations in Bangladeshi patients with adenocarcinoma of the lung

Abstract: The present study revealed that the EGFR mutation rate in Bangladeshi patients with adenocarcinoma of the lung was higher than in African-American, Arabian, and white Caucasian patients, and was lower than in East Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Other studies from India have also shown similar female predominance in EGFR mutation [1, 17]. A study from Bangladesh reported an exception to this pattern where Rahman et al reported higher EGFR mutation rate in men than women (25.5% men, 14.3% women) [18].…”
Section: Discussionmentioning
confidence: 78%
“…Other studies from India have also shown similar female predominance in EGFR mutation [1, 17]. A study from Bangladesh reported an exception to this pattern where Rahman et al reported higher EGFR mutation rate in men than women (25.5% men, 14.3% women) [18].…”
Section: Discussionmentioning
confidence: 78%
“…Tanaka et al 4 East Asian (Japan) 104/242 (43%) Choi et al 5 East Asian (Korea) 203/521 (39%) Rahman et al 11 South Asian (Bangladesh) 14/61 (23%) Castro et al 6 White 29/216 (13%) Smits et al 10 White 66/620 (11%) This study North African 29/137 (21%) EGFR, epidermal growth factor receptor. Huang et al 7 Asian 35 48 Shigematsu et al 8 American 44 41 Castro et al 6 White 39 33 De Mello et al 12 White 50 45 This study North African 69 21…”
Section: Race Egfr Mutation (%)mentioning
confidence: 77%
“…Some previous studies have demonstrated a genetic divergence of EGFR mutation rates according to ethnicity. [4][5][6]10,11 Indeed, the EGFR mutation rate in East-Asian patients (39%-43%) is much higher than that of the white population (11%-13%) whereas some races, such South-Asian, have an intermediate rate (23%). EGFR mutation frequency in Moroccan patients, as reported in this study, is higher than that found in whites but lower than in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of EGFR mutations is much higher in individuals of Asian origin (45-50%) than in individuals from Western Europe (10-15%) or North America (15-20%). It is noteworthy that high variability has been reported in the prevalence of EGFR mutations within the Asian-Pacific population, with a higher frequency in Vietnam (64.2%), Thailand (53.8%) and China (50.2%) than in India (22.2%) or Bangladesh (23%) [70,71]. This variability has also been observed in South America, with a higher proportion of EGFR mutations among the Amerindian subpopulation (principally Peru, 67%, but also Mexico, 31.2%, and Colombia, 24.8%) compared to Caucasian populations (Argentina, 19.3%) [72].…”
Section: Epidemiologymentioning
confidence: 99%